SOME ASPECTS OF PROMOTING REPRODUCTIVE HEALTH AMONG YOUNG PEOPLE - I.E.Ravshanova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article will help to promote reproductive health among young people to ensure that the younger generation is healthy, harmonious and mature given the lighting.